Determinants of the spatial structure of employment in Cartagena - Yánez Contreras, Marta; Acevedo González, Karina (Sociedad y Economía, 2010)
This paper makes an approach to the determinants of employment spatial structure in Cartagena over the year 2005. To that purpose, the employment location pattern is described and characterized, and then, spatial models are estimated. The results show as the main determinants to the proximity to an important avenue, the demand (manly in the commerce and service) and the presence of the agglomerations economies (mostly in the industry).